2018
DOI: 10.1088/1361-648x/aaa274
|View full text |Cite
|
Sign up to set email alerts
|

Hydrodynamics of electrons in graphene

Abstract: Generic interacting many-body quantum systems are believed to behave as classical fluids on long time and length scales. Due to rapid progress in growing exceptionally pure crystals, we are now able to experimentally observe this collective motion of electrons in solid-state systems, including graphene. We present a review of recent progress in understanding the hydrodynamic limit of electronic motion in graphene, written for physicists from diverse communities. We begin by discussing the "phase diagram" of gr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
475
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 357 publications
(487 citation statements)
references
References 277 publications
(889 reference statements)
9
475
0
3
Order By: Relevance
“…In typical 1D and 2D carbon structures,t here are two main vacancies types:1 )single-atom vacancies and 2) multi-atom vacancies.T he vacancies usually lead to fluctuations in the local electron spin and density,a sw ell as the atomic relaxation at the boundary. [33] Recently,X ia and co-workers reported ac omprehensive analysis regarding the lattice defects in graphene,w hich involved various single-atom vacancy configurations.According to the charge and spin density analyses,itwas found that the regulation of electronic structure by vacancy construction could significantly enhance the catalytic activity of perfect graphene. [34] Baek et al simulated the edge-molecule orbital configuration of sulfurized graphene nanoplatelets.T hey proposed that the introduced sulfur atoms are beneficial to the electron-transfer process during ORR.…”
Section: Non-metal Materialsmentioning
confidence: 99%
“…In typical 1D and 2D carbon structures,t here are two main vacancies types:1 )single-atom vacancies and 2) multi-atom vacancies.T he vacancies usually lead to fluctuations in the local electron spin and density,a sw ell as the atomic relaxation at the boundary. [33] Recently,X ia and co-workers reported ac omprehensive analysis regarding the lattice defects in graphene,w hich involved various single-atom vacancy configurations.According to the charge and spin density analyses,itwas found that the regulation of electronic structure by vacancy construction could significantly enhance the catalytic activity of perfect graphene. [34] Baek et al simulated the edge-molecule orbital configuration of sulfurized graphene nanoplatelets.T hey proposed that the introduced sulfur atoms are beneficial to the electron-transfer process during ORR.…”
Section: Non-metal Materialsmentioning
confidence: 99%
“…A new drag system consisting of 2D graphene and a confined 1D nanowire or nanotube, not only has a potential for probing the graphene locally, but also the dimensionally mismatched Coulomb drag system can potentially become the foreground for studying the effect of dimension on scattering mechanisms in Coulomb drag [25,26]. This kind of drag system is expected to show novel quantum phases in the strong coupling regime [27] in addition to being a tool for studying the graphene hydrodynamics near the Dirac point [28]. With this motivation we have carried out the Coulomb drag experiments in MLG-InAs NW and BLG-InAs NW devices as a function of density (n), temperature (T ) and magnetic field (B).…”
mentioning
confidence: 99%
“…Tr Tr , the prefactor 2 marks the spin degeneracy (we neglect the Zeeman effect 4 ), and = x x x † T t t with x t being the transmission matrix for one valley. We further neglect the electron-electron interaction and electron-phonon coupling, which is acommon approach to nanosystems in monolayer graphene close to the Dirac point, as the scattering processes associated with these many-body effects are usually slower than the ballistic-transport processes [48,49].…”
Section: Mode-matching In the Angular-momentum Spacementioning
confidence: 99%